Post Covid-19 Pandemic New Marketing Theories and Practices Emerging from Innovations in the Tourism Sector. - zaenal aripin; vip Paramarta; Kosasih (Journal of Jabar Economic Society Networking Forum, 2023)
Abstract - The tourism sector has a very important role in life in various sectors and also in various countries. In 2015 the tourism sector contributed 10% of Indonesia's total GDP with the highest nominal amount in ASEAN. However, since the covid-19 pandemic there has been a decrease in the number of tourist visitors in various tourism sites. The method used is with data collection techniques through literature studies, and also quantitative data processing from BPS data in 2022, based on the results obtained, the marketing strategy applied in this study is, by researchers in applying the toursime city branding strategy and also DOT, BASE and POSE in developing marketing strategies for the post-pandemic covid-19 tourism sector in Indonesia, then there are some insights and also an increase in the number of tourists visiting tourism in Indonesia.